KOMODIFIKASIAN OJEK PANGKALAN DALAM ARENA DEMOKRASI LOKAL (Studi Kasus di Pemilihan Walikota Sorong Tahun 2017) - Arie Purnomo, Bustamin Wahid, (Jurnal Noken: Ilmu-Ilmu Sosial, 2019)
This research is entitled: Commodification ofÂ Base Ojek Services in the Arena of Democracy (Case Study of Sorong City Election in 2017). Researchers try to review local political phenomena in Sorong West Papua by utilizing social solidarity ojek base in the interests of political power. Because ojek services are not just public transportation services but now base motorcycle taxi services are now a new social strength and capital that can be commercialized in political interests. In this study, the researchers formulated two questions: (1) How was the involvement of base taxi drivers in the elections in the city of Sorong in 2017? (2) What is the impact of modification of base taxi in the elections in Sorong city in 2017? With the existing research focus, the researchers used modification theory, political theory, social solidarity and knowledge of ojek services as theoretical legitimacy to direct and analyze this research so that it could provide adequate outcomes. This study uses a qualitative approach and descriptive method, with the aim of describing existing phenomena, which occur at this time or in the past. This study does not carry out manipulation or alteration of independent variables but tries to describe in accordance with the real reality, about content and research focus. Of course with great hope that this research can provide scientific and beneficial effects for many people and become an evaluation material for party institutions (political parties) in providing political education to the public. Especially for people who move as ojek (motorcycle taxi) bases. The output of this study can also add to the discourse and study of local politics which is increasingly complex to the social foundations of society.